AVALIAÇÃO DA RECUPERAÇÃO DE SANGUE INTRA E PÓS-OPERATÓRIA EM PACIENTES SUBMETIDOS À CIRURGIA CARDÍACA COM CIRCULAÇÃO EXTRACORPÓREA - Marco Antonio Araujo de Mello (2024)
The scarcity of blood in the world has become even more evident with the COVID-19 Pandemic. The World Health Organization in October 2021 recommended the implementation of the protocol for Patient Blood Management, whose acronym in English is “PBM”, as a matter of urgency. Reducing blood loss during surgery is the second of the three pillars of “Patient Blood Management” (PBM). The use of cell saver in cardiac surgery is proposed to reduce intraoperative blood loss and thus reduce the consumption of stored red blood cell concentrate units. This equipment can be used both intraoperatively and in the immediate postoperative period connected to the patient's drains. This study aimed to evaluate the impact of using the blood cell saver in the intraand postoperative periods on hematocrit and hemoglobin values, on the transfusion of blood components, and on the length of hospital stay in patients undergoing cardiac surgery with cardiopulmonary bypass. The study design is a concurrent, non-randomized, multicenter cohort conducted at Hospital Universitário Maria Aparecida Pedrossian (HUMAP), Hospital UNIMED Campo Grande and Hospital CASSEMS Campo Grande between April 2021 and July 2023. Participants were individuals who required heart surgery using cardiopulmonary bypass (CPB), regardless of the surgical cause, of both sexes and over 18 years of age. The patient sample was for convenience and consisted of 41 patients divided into two groups (A and B). The patients at Hospital UNIMED Campo Grande and Hospital CASSEMS Campo Grande (group A) totaled 21 individuals and were operated on using the cell saver. The patients at Hospital Universitário Maria Aparecida Pedrossian (HUMAP) (group B) totaled 20 individuals and were operated on without using the aforementioned equipment. With this study, we were able to conclude that with the use of a blood cell retriever intraoperatively and in the immediate postoperative period (24 hours) in patients undergoing cardiac surgery with cardiopulmonary bypass, less blood loss was achieved intraoperatively and immediately postoperatively, shorter hospital stay (total or postoperative), lower consumption of allogeneic red blood cell concentrate units and higher postoperative hematocrit. As expected, it was observed that the preoperative hemoglobin value influenced the number of bags administered postoperatively, showing the need to treat anemia preoperatively. The lower the Hb value, the greater the need for allogeneic red blood cell transfusion. The days of hospital stay also had an effect on the final average number of blood bags administered postoperatively. The greater the number of days of hospital stay, the greater the need for blood transfusion.